Doxycycline Reduces Scar Thickness and Improves Collagen Architecture. Issue 1 (July 2020) - Moore, Alessandra L.; desJardins-Park, Heather E.; Duoto, Bryan A.; Mascharak, Shamik; Murphy, Matthew P.; Irizarry, Dre M.; Foster, Deshka S.; Jones, Ruth E.; Barnes, Leandra A.; Marshall, Clement D.; Ransom, Ryan C.; Wernig, Gerlinde; et al.
Abstract : Objective: To investigate the effects of local doxycycline administration on skin scarring. Background: Skin scarring represents a major source of morbidity for surgical patients. Doxycycline, a tetracycline antibiotic with off-target effects on the extracellular matrix, has demonstrated antifibrotic effects in multiple organs. However, doxycycline's potential effects on skin scarring have not been explored in vivo. Methods: Female C57BL/6J mice underwent dorsal wounding following an established splinted excisional skin wounding model. Doxycycline was administered by local injection into the wound base following injury. Wounds were harvested upon complete wound closure (postoperative day 15) for histological examination and biomechanical testing of scar tissue. Results: A one-time dose of 3.90 mM doxycycline (2 mg/mL) within 12 hours of injury was found to significantly reduce scar thickness by 24.8% ( * P < 0.0001) without compromising tensile strength. The same effect could not be achieved by oral dosing. In doxycycline-treated scar matrices, collagen I content was significantly reduced ( * P = 0.0317) and fibers were favorably arranged with significantly increased fiber randomness ( * P = 0.0115). Common culprits of altered wound healing mechanics, including angiogenesis and inflammation, were not impacted by doxycycline treatment. However, engrailed1 profibrotic fibroblasts, responsible for scar extracellular matrix deposition, were significantly reduced with doxycycline treatment ( * P = 0.0005). Conclusions: Due to the substantial improvement in skin scarring and well-established clinical safety profile, locally administered doxycycline represents a promising vulnerary agent. As such, we favor rapid translation to human patients as an antiscarring therapy. Abstract : Supplemental Digital Content is available in the text